Raziskovanje kognitivnih shem kot individualnih ali skupinskih struktur - Arzenšek, Ana (Psihološka obzorja (Ljubljana), 2012)
The present paper describes some features of the theory of cognitive schemas. The discussion focuses on the issue of appropriate level to explore the cognitive schemas: the individual-, above individual- or the level of larger social systems, depending on the characteristics of social cognition and the nature of cognitive schemas. Currently researchers of cognitive schemas focus on the interaction between motivational, cognitive and other personal and situational variables and on their influence on behavior. Cognitive schemas are seen as the result of mutual interplay between personal, environmental and situational variables. The answer to the appropriate level of exploration question is found to depend on the paradigm within which the individual researchers work and also on the nature of the research problem.
Keywords: kognitivne sheme; schema; social cognition; socialna kognicija; socialna psihologija; theories; social psychology; raziskovanje; experimentation